Employer market power in Silicon Valley - Matthew Gibson (W.E. Upjohn Institute for Employment Research, 2024)
Adam Smith alleged that employers often secretly combine to reduce labor earnings. This paper examines an important case of such behavior: illegal no-poaching agreements through which information-technology companies agreed not to compete for each other's workers. Exploiting the plausibly exogenous timing of a U.S. Department of Justice investigation, I estimate the effects of these agreements using a difference-in-difference design. Data from Glassdoor permit the inclusion of rich employer- and job-level controls. On average the no-poaching agreements reduced salaries at colluding firms by 5.6 percent, consistent with considerable employer market power. Stock bonuses and job satisfaction were also negatively affected.
Keywords: J42; K42; L41; K21; 330; No-poach agreement; employer market power; Silicon Valley; tech companies; Glassdoor; compensation